An Evaluative Study Of The Use Of Sim (Management Information System) In Integrated Islamic Schools - Miftahul Janah (Jurnal Ekonomi islam and Manajemen, 2025)
This study aims to evaluate the use of Management Information System (MIS) in Integrated Islamic Schools (SIT) as an effort to improve the quality of education services. SIM is expected to be able to help the administrative process, data management of students, teachers, and finances more efficiently. The research method used was descriptive evaluative with qualitative and quantitative approaches. Data were obtained through observations and interviews distributed to teachers, education personnel and school principals. The results showed that the use of SIM has been quite helpful in managing academic and financial data, but there are still obstacles such as limited human resource competence in operation, limited infrastructure, and lack of system integration. The recommendations of this study are the need for continuous training, development of features that suit the needs of Islamic schools, and strengthening information technology infrastructure.